Phytochemicals, Antihemolytic, Anti-inflammatory, Antioxidant, and Antibacterial Activities from Thymus Algeriensis. Issue 3 (3rd July 2021) - Mokhtari, Mouna; Chabani, Sonia; Mouffouk, Soumia; Aberkane, Mohamed-Cherif; Dibi, Ammar; Benkhaled, Mohammed; Haba, Hamada
ABSTRACT: The chemical composition and anti-inflammatory, antihemolytic, antioxidant, and antibacterial activities of solvent extracts of Thymus algeriensis in petroleum ether, chloroform, and n -butanol were evaluated. Ten compounds including four flavonoids, four phenolics, and two triterpenoids were isolated and identified by chromatography and spectroscopy. The n -butanol extract had the greatest antioxidant activity and inhibited hemolysis with a value of IC50 at 322.85 ± 0.87 µg mL −1 . The chloroform extract exhibited the highest anti-inflammatory effect with 45.27% inhibition. The extracts demonstrated antibacterial activity against the tested strains.